Market Proximity Agrarian Solidarity and Forest Fringe Institutions Shaping Household Resilience in Rural Poverty Contexts - Purnamansyah, Nanda Andi; Ismiati, Arini (Future Space: Studies in Geo-Education, 2026)
While poverty is often measured economically, its spatial dimension how location dictates survival strategies remains under-explored. This study analyzes how spatial context influences social interaction patterns among economically vulnerable households in Dampit Village, Malang Regency. A qualitative case study was conducted from June 1–28, 2024 , across five distinct neighborhood zones (Wards). Data were collected through semi-structured interviews with 10 purposively selected participants (5 key informants from vulnerable households and 5 village stakeholders) , participatory observation, and spatial mapping. Analysis utilized an inductive thematic approach triangulated with spatial data. Findings reveal that interaction patterns are spatially determined: (1) In market-proximate zones (West Dampit), interactions are transactional and driven by trade reciprocity; (2) In agrarian zones (Sumber Kembar), interactions rely on "harvest solidarity" and labor sharing; and (3) In forest-fringe areas (Ngelak), interactions are institutionalized through Forest Village Institutions (LDH) for land management. This study extends poverty research by demonstrating that "survival" is a place-based phenomenon. These findings serve as a vital place-based inquiry resource for geography education, specifically to teach concepts of spatial inequality and community resilience using local contextual examples.